Pengembangan Lapisan Mode Gerak Agen pada Robot Soccer - Mindit Eriyadi (Universitas Pendidikan Indonesia, 2016)
Soccer robot is an international project that aims to support research in the field of artificial intelligence systems, robotics, independent agent, and other disciplines that have linkages with the things mentioned above. This research aims to design generally wake a system mirosot the host side development into a client server system. Specifically aims to develop the concept of motion modes coating robot soccer agent. The next layer motion mode robot soccer agent is used to develop the ability of the agent and the team. Coating agent robot motion mode is one part in the design of the robot soccer team. Coating agent robot motion mode has been designed and implemented in the form of layers - layer agent robot motion mode. Each layer motion mode robot agent can be used in accordance with the environment and the desired targets. Design coating agent motion mode is done by dividing the motion mode agent into several layers of motion with the aim to facilitate the testing, implementation and development. This research has resulted in the design of a total of 20 modes of motion are divided into 3 layers motion robot agent.